Avaliação do Programa de Aprendizagem na Idade Certa (MAIS PAIC): o Sistema Permanente de Avaliação Educacional do Ceará (SPAECE) no município de Aquiraz - Sousa, Suzanne Albano de (2024)
In the Brazilian educational scenario, among the countless challenges that exist in the field of public education, the issue of investment in quality education, which is provided for by law, must be implemented by all spheres of government, be they federal, state or municipal. As a way of checking the country's educational situation, and also as a means of generating public policies aimed at the quality of education, the Ministry of Education and Culture (MEC) began to adopt large-scale assessment policies primarily to measure school performance, find out about the socio-economic, cultural and school situation of students, research the profile and management practices of principals and investigate the profile and pedagogical practices of teachers and the infrastructure of schools. Thus, with a view to quality public education, focused on raising the level of learning offered to students in Ceará, the Learning at the Right Age Program (MAIS PAIC) was created, with the main objective of overcoming school illiteracy. In order to find elements that contribute to the construction of knowledge and discussions about obtaining results on the MAIS PAIC evaluation axis expressed in the external evaluation system Sistema Permanente de Avaliação Educacional do Ceará - SPAECE (Permanent Educational Evaluation System of Ceará), the general objective of this research is to evaluate MAIS PAIC by comparing the results obtained in SPAECE in 2nd grade elementary school classes in the municipal network of Aquiraz CE. The methodological approach consisted of a qualitative bibliographical and documentary review, under the influence of in-depth evaluation, to assess the proficiency levels of the SPAECE-ALFA (2012-2022), the performance standards and the School Performance Index (IDE) of two schools in the municipality of Aquiraz-CE. The main results of the study showed that, although the impacts and consequences of the COVID-19 pandemic on the education of children in Aquiraz were evident, it was observed that Ceará education in the municipality, based on the SPAECE-ALFA data from the schools in the sample, has been promoting a qualitative leap in student learning.